USE OF SOFTWARE IN PHYSICS LEARNING PROCESS - Farmonov, Utkir; Isoqov, Shohrux (Физико-технологического образование, 2021)
This article describes the content of the organization of educational processes in the field of physics and astronomy on the basis of modern software. Opportunities to increase student creativity on the basis of modern tools have been identified